RISK FACTORS IN PULMONARY TUBERCULOSIS TREATMENT FAILURE - Dyan Kunthi Nugrahaeni; Lala Rosmalaningrum (Universitas Airlangga, 2021)
Pulmonary tuberculosis (TB) is a global health problem and has become the leading cause of death. Tuberculosis eradication is inhibited due to the tendency of patients to not complete the TB treatment. The purpose of this study was to determine the relationship between knowledge, nutritional status, oral medication adherence, and family support as risk factors for pulmonary tuberculosis treatment failure. The design of this study is that of case-control, and this study involved samples of pulmonary TB patients who were declared not cured after treatment (14 people), and control samples of pulmonary TB patients who were declared cured (28 people). The data were obtained through measurements of nutritional status and interviews, while treatment failure was based on data from the TB 01 form. Data was analysed using univariable and bivariable analyses, and the magnitude of risk factors was based on the odds ratio (OR) and 95% confidence interval (CI). The results showed that the factors associated with failure of pulmonary TB treatment are knowledge (p = 0.022; OR = 6.6; 95% CI = 1.48 - 29.36), nutritional status (p = 0.005; OR = 9.16; 95% CI = 2.11 - 39.85), and medication adherence (p = 0.003; OR =11.0; 95% CI = 2.37 - 54.14), whereas the unrelated factor is family support (p = 0.47). It is recommended to provide counselling, nutritional guidance, medication assistance, and family support to patients during the treatment period for pulmonary tuberculosis. Keywords: treatment failure, knowledge, nutritional status, compliance